AVIAN DIVERSITY OF LAHORE ZOO SAFARI IN WINTER SEASON LAHORE, - H. Raza; S. Mehmood; B. N. Khan; F. Bibi; Z. Ali (Journal of Animal and Plant Sciences, 2015)
The study was carried out to observe the avian diversity during winter season at Lahore Zoo safari. Lahore zoo safari is 0 ’ 0 ’ located in (31 22 57 N, 74 12 47 E and elevation 208m) district Lahore, Punjab, Pakistan. The ecosystem is a composite of wetland, terrestrial and irrigated plantation. The survey was carried out from October 2014 to December 2014 to record the bird diversity. A total 2085 birds belonging to 52 species covering 30 families and 12 orders were observed. The season wise distribution was resident were 37 (71.1%), winter migratory 11 (21.1%), and summer breeder 4 (7.6%). Shannon-Weiner diversity index 1.93 shown a low profile of avian diversity along with, Simpson ’s diversity 2 index 0.64, species evenness 0.49, species richness 52 and census index was 1021.7 birds/km . Among the most dominant species were House crow Corvus splendens (n=600), House sparrow Passer domesticus (n=85), Common myna Acridotheres tristis (n=63), Jungle babbler Turdoides striatus (n=50) and Black crowned night heron Nycticorax nycticorax (n=30). 1981. The ecosystem that is composite of wetland,
Keywords: Diversity indices; Urbanization; Winter Diversity; Lahore Zoo Safari.